Low‐Voltage, High‐Frequency Organic Transistors and Unipolar and Complementary Ring Oscillators on Paper. (26th November 2018) - Kraft, Ulrike; Zaki, Tarek; Letzkus, Florian; Burghartz, Joachim N.; Weber, Edwin; Murmann, Boris; Klauk, Hagen
Abstract: Paper substrates for flexible, mobile, and disposable electronic applications draw academic and commercial attention due to their many advantages, such as cost efficiency, low weight, mechanical flexibility, and environmental compatibility. For portable electronic applications, it is important that the electronic devices and circuits can be operated with voltages of a few volts, due to the limitations of mobile power supplies, such as solar cells or energy harvesting devices. Here, low‐voltage organic p‐channel and n‐channel transistors as well as unipolar and complementary ring oscillators are fabricated directly on the surface of a banknote. It is demonstrated that low‐power organic integrated circuits on paper substrates can be operated with supply voltages of less than 3 V and with frequencies of several hundred kilohertz. These results emphasize the prospects of organic transistors for smart paper applications. Abstract : Low‐power organic integrated circuits on paper substrates are operated with supply voltages of less than 3 V and frequencies of several hundred kilohertz. These results emphasize the prospects of organic transistors for smart paper applications. Organic p‐channel (carrier mobility: 1.1 cm 2 Vs ‐1 ) and n‐channel transistors (0.17 cm 2 ) as well as ring oscillators are fabricated directly on the rough surfaces of banknotes.